FAKTOR-FAKTOR YANG MEMENGARUHI MINAT BELI PADA APLIKASI TIKTOK SHOP - Kairupan, Daniel Joel Immanuel; Fakih, Yuda (LPPM STIE YKPN Yogyakarta, 2024)
This research aims to investigate the influence of Electronic Word of Mouth (E-WOM), advertising, and ease of transactions on purchasing interest in the TikTok Shop application. A quantitative approach was used in this research using a questionnaire as a data collection tool. The respondents involved in this research were active users of the TikTok Shop application. Data were analyzed using the multiple linear regression method with SPSS 22 for the analytic tools. This research provides an important contribution to the understanding of the factors that influence purchasing interest in the TikTok Shop application. The practical implication of this research is that marketing managers can pay attention to and improve E-WOM strategies, advertising, and ease of transactions to increase consumer buying interest in the TikTok Shop application.